2019
DOI: 10.1159/000497317
|View full text |Cite
|
Sign up to set email alerts
|

History of Lifetime Cannabis Use Is Associated with Better Cognition and Worse Real-World Functioning in Schizophrenia Spectrum Disorders

Abstract: Background: Data on associations between cannabis use and psychopathology, cognition and functional impairment in schizophrenia spectrum disorders (SSD) is controversial. Objectives: To examine the effect of cannabis on psychopathology, cognition and real-world functioning in SSD patients. Method: Naturalistic cross-sectional study, 123 clinically stable SSD outpatients. Assessment: demographic and clinical data, psychometric evaluation: Positive and Negative Syndrome, Hamilton Depression Rating, Clinical Glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
5
0
3
Order By: Relevance
“…Filbey et al 2021;Schacht et al, 2012;Taurisano et al, 2021), psychiatric comorbidities (e.g. Bogaty et al, 2018;Menendez-Miranda et al, 2019;Wallace et al, 2019), and lifestyle factors that influence brain health (Lisdahl et al, 2014). For the latter, this Special Issue includes an article by Sullivan and colleagues reporting novel relationships between aerobic fitness, cannabis use and brain volume in healthy adolescents and young adults.…”
Section: Potential Moderators Of Cannabis-related Effectsmentioning
confidence: 99%
“…Filbey et al 2021;Schacht et al, 2012;Taurisano et al, 2021), psychiatric comorbidities (e.g. Bogaty et al, 2018;Menendez-Miranda et al, 2019;Wallace et al, 2019), and lifestyle factors that influence brain health (Lisdahl et al, 2014). For the latter, this Special Issue includes an article by Sullivan and colleagues reporting novel relationships between aerobic fitness, cannabis use and brain volume in healthy adolescents and young adults.…”
Section: Potential Moderators Of Cannabis-related Effectsmentioning
confidence: 99%
“…Las tipos de memoria evaluados en los diferentes estudios han sido diversos, memoria visual (Sanchez-Torres et al, 2013;Yucel et al, 2012), verbal (Rabin et al, 2017;Sanchez-Torres et al, 2013;Schnell et al, 2009;Setien-Suero et al, 2018), episódica (Mallet, Ramoz, Le Strat, Gorwood, y Dubertret, 2017), inmediata (Nunez et al, 2016), de trabajo (Gonzalez-Pinto et al, 2016;Meijer et al, 2012;Menendez-Miranda et al, 2019;Nunez et al, 2016;Schnell et al, 2009;Yucel et al, 2012) o a largo plazo (Nunez et al, 2016). Asimismo, los datos de los mismos no son concluyentes.…”
Section: Variables Neurocognitivasunclassified
“…Asimismo, los datos de los mismos no son concluyentes. En pacientes con esquizofrenia con historia de consumo de cannabis en algunos casos se ha observado una mejor adquisición de conocimiento (Meijer et al, 2012), mejor desempeño en tareas de memoria (DeRosse et al, 2010;Menendez-Miranda et al, 2019), incluso pacientes que habían sido consumidores graves antes del inicio de la enfermedad parecían mostrar una mejor memoria episódica (Mallet et al, 2017). Sin embargo, en hermanos de pacientes con esquizofrenia una historia de consumo de cannabis a lo largo de la vida se ha asociado con un efecto negativo en la memoria declarativa, tanto visual como verbal (Sanchez-Torres et al, 2013).…”
Section: Variables Neurocognitivasunclassified
See 1 more Smart Citation
“…Globally, 21 million people suffer from schizophrenia 1 . The high prevalence of cannabis use in schizophrenia is well-established, with lifetime rates of 53.7% 2 . A meta-analysis found that 25% of people with schizophrenia have cannabis use disorder (CUD) 3 compared to ~3% in general population 4 .…”
Section: Introductionmentioning
confidence: 99%